Schizophyllum commune induced genotoxic and cytotoxic effects in Spodoptera litura - Mandeep Kaur (Nature Portfolio, 2018)
Abstract In search for ecofriendly alternatives to chemical insecticides the present study was conducted to assess the insecticidal potential of an endophytic fungus Schizophyllum commune and its mechanism of toxicity by studying genotoxic and cytotoxic effects as well as repair potential using Spodoptera litura (Fabricius) as a model. Different endophytic fungi were isolated and tested for their insecticidal potential against S. litura. Among the tested endophytic fungi maximum mortality against S. litura was exhibited by S. commune isolated from Aloe vera. Extended development, reduced adult emergence was observed in larvae fed on diet supplemented with fungal extract. In addition to it the fungus also has propensity to increase oxidative stress which leads to significantly higher DNA damage. The significantly lower frequency of living haemocytes and increased frequency of apoptotic and necrotic cells was also observed in larvae treated with fungal extract. The extent of recovery of damage caused by fungus was found to be very low indicating long term effect of treatment. Phytochemical analysis revealed the presence of various phenolics, terpenoids and protein in fungal extract. Biosafety analysis indicated the non toxic nature of extract. This is the first report showing the insecticidal potential of S. commune and the genotoxic and cytotoxic effects associated with it.